2018
DOI: 10.37358/rc.18.7.6432
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antioxidant Components and Activity of Tamarix ramosissima Comparative with Vaccinium myrtillus on Streptozotocin-diabetic Mice

Abstract: Tamarix ramosissima (Tamaricaceae) is a small tree that grows spontaneously in Europe and Asia, being considered an invasive species in geographical areas with warm climates. The chemical composition is partially elucidated, being empirically used for antiinflammatory, analgesic, antibacterial and antioxidant effect. Our study aimed to evaluate the total polyphenol and flavonoid content of vegetal extracts and to test in vivo antioxidant therapeutic effect of it, comparative with Vaccinium myrtillus, using str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Previous studies revealed that elevation in HDL-C is associated with lowering the CVD development risk [23]. The lipid-lowering potential of OSE might be linked to the https://doi.org/10.37358/RC.20.11.8379 presence of phytocompounds, such as flavonoids [24].…”
Section: Effect Of Treatments On Lipid Profilementioning
confidence: 99%
“…Previous studies revealed that elevation in HDL-C is associated with lowering the CVD development risk [23]. The lipid-lowering potential of OSE might be linked to the https://doi.org/10.37358/RC.20.11.8379 presence of phytocompounds, such as flavonoids [24].…”
Section: Effect Of Treatments On Lipid Profilementioning
confidence: 99%
“…All measurements of oxidative stress biomarkers were carried out using a Beckman UV-Vis DU-65 spectrophotometer equipped with a temperature control module (Beckman Instruments, Fullerton, United States). All experimental measurements were carried out in triplicate and are expressed as average of three analyses ± standard deviation [16].…”
Section: Determination Of Total Carotenoids and Chlorophylls A And Bmentioning
confidence: 99%
“…Nowadays, according to the WHO, natural therapies are widely used by the world's population [5], because medicinal plant parts are commonly rich in phenolic compounds, such as flavonoids, phenolic acids, stilbenes, tannins, coumarins, lignans and lignins with remarkable pharmacological effects [6]. In vitro studies have shown that plants have antibacterial efficacy against many bacterial species, revealing the importance of natural resources, little studied in this respect, in the fight against bacterial resistance and the destruction of bacterial agents [7].…”
mentioning
confidence: 99%